PERBANDINGAN PENYARADAN KAYU DENGAN SISTIM MANUAL DAN EKSAVATOR DI HUTAN RAWA BAGIAN Ill : KAJIAN TEKNIS, EKONOMIS DAN EKOLOGIS - Wesman Endom; Zakaria Basari (Jurnal Penelitian Hasil Hutan, 2001)
Modified excavator is one of heavy equipment that might be useful and environmentally friendly to be used for operational logging extraction especially in swampforest. It is therefore besides convenient and powerful, it is also helpful as an effective alternative in anticipating the weakness of manual system which is called "kuda-kuda'.Related to the case, a study by implementing both manual system and excavator was done in a forest concession, i.e. PT. Inti Prona, at cutting block covering the 1997/1998 area that located under management of Sub Forest District Dumai, Riau Province. The study covered aspects of extraction productivity, extraction cost, and logging impact on the possible damage of residual forest stands due to the implementation of both systems.The result showed that the average of logs extraction productivity was 16.80 m3.hm per hour. With respect to the ecological impacts, it was found that residual forestst and damage occurred at 17.29% per ha (at pole stage) and 17.17% per ha (at tree stage). Further, operation cost hauling was assessed at Rp 5,600 per m3 of extracted log.Meanwhile, manual log extraction revealed productivity at 2,46 m3.hm per hour. Ecological impact due to constructionsof manual road extraction system and landing site (TPn) was the occurrence of damage to pole and tree stages at 28,25% and 34,33%, respectively. In the same occasion, cost of manual extraction was about Rp 23.000 per m3.Keywords : excavator, productivity, damage, tree, poles and extraction cost